Stephen P. Turner, The Search For a Methodology of Social Science. Durkheim, Weber the Problem of Cause, Probability, and Action, Dordrecht/Boston/Lancaster/Tokyo: Reidel Publishing Company, 1986, 251 s., kr. 540,00. - Jensen, Henrik (Politica, 1989)
-